2010
DOI: 10.1123/jsep.32.3.377
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Psychological Momentum in Sport: The Role of Ongoing History of Performance Patterns

Abstract: Borrowing the dynamical systems perspective, two studies aimed to examine the potential properties of nonlinearity and history dependence of psychological momentum. Male regional-level table tennis players were asked to empathize with players in a very important contest by watching two video scenarios of a table tennis game in two separate sessions. The videos presented two inverted scenarios in which score gaps gradually increased or decreased. Competitive anxiety, self-confidence (Study 1), and goal involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
124
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(151 citation statements)
references
References 55 publications
15
124
2
10
Order By: Relevance
“…This may be especially pertinent in soccer where the outcome of the match has large financial implications (Hoffmann, Ging, & Ramasamy, 2002). The term "momentum" is frequently used to describe where the sequence of scoring or winning (success) has an influence on future performance success (Briki, Den Hartigh, Markman, Micallef, & Gernigon, 2013;Gernigon, Briki, & Eykens, 2010;Iso-Ahola & Dotson, 2014;Taylor & Demick, 1994;Vallerand, Colavecchio, & Pelletier, 1988). In contrast, "psychological momentum" (PM) is a term used in sport psychology that captures not only the success -future performance relationship, but also shifts in affect, cognition and behaviour in either a positive or negative direction in athletes, coaches and fans (Jones & Harwood, 2008;Markman & Guenther, 2007;Perreault et al, 1998;Taylor & Demick, 1994;Vallerand et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be especially pertinent in soccer where the outcome of the match has large financial implications (Hoffmann, Ging, & Ramasamy, 2002). The term "momentum" is frequently used to describe where the sequence of scoring or winning (success) has an influence on future performance success (Briki, Den Hartigh, Markman, Micallef, & Gernigon, 2013;Gernigon, Briki, & Eykens, 2010;Iso-Ahola & Dotson, 2014;Taylor & Demick, 1994;Vallerand, Colavecchio, & Pelletier, 1988). In contrast, "psychological momentum" (PM) is a term used in sport psychology that captures not only the success -future performance relationship, but also shifts in affect, cognition and behaviour in either a positive or negative direction in athletes, coaches and fans (Jones & Harwood, 2008;Markman & Guenther, 2007;Perreault et al, 1998;Taylor & Demick, 1994;Vallerand et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest was the antecedents-consequences model (AC) proposed by Vallerand et al (1988), which was followed by the multi-dimensional model (MD) (Taylor & Demick, 1994), and the projected performance model (PP) (Cornelius et al, 1997). More recently, Gernigon et al (2010) proposed that PM could be described as a dynamical system, where the system or team, in the case of most sporting examples does not vary as a function of one or two independent variables (e.g., triggers) but as a function of its preceding state (e.g., whether the team is in a stable or unstable state). The view is supported by qualitative research (Briki, Den Hartigh, Hauw, & Gernigon, 2012;Jones & Harwood, 2008) which reported a number of PM variables as both determinants and consequences of PM states.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result suggests that AI had psychological momentum. Psychological momentum means a power that increases in relation to the decrease in the opponent's involvement (e.g.. Gemigon, Briki, & Eykens, 2010). This power changes the perception of oneself and the opponent, influences the belief that the result will be success, and improves or maintains involvement in the match.…”
Section: The Story Behind the Storymentioning
confidence: 99%